If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -91 = 9t + 8 Reorder the terms: -91 = 8 + 9t Solving -91 = 8 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -91 + -9t = 8 + 9t + -9t Combine like terms: 9t + -9t = 0 -91 + -9t = 8 + 0 -91 + -9t = 8 Add '91' to each side of the equation. -91 + 91 + -9t = 8 + 91 Combine like terms: -91 + 91 = 0 0 + -9t = 8 + 91 -9t = 8 + 91 Combine like terms: 8 + 91 = 99 -9t = 99 Divide each side by '-9'. t = -11 Simplifying t = -11
| 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) | | 7-8x=127-39x | | z^2-15=0 | | 3(x+7m+5)= | | 3x-12=4x-12 | | 50(x)=-0.4x^2+80x-1600 | | -21=7y | | 5(x+2)-7(x-1)=1 | | c+5=3 | | (8z-2)(8-z)=0 | | x(7x+32)+33=0 | | 2m=m+6 | | 5x^2+6x=31 | | -x-5=6 | | (n-4)*3=15 | | 20-c=12 |